Substitusi Tepung Ikan dan Bungkil Kedelai dengan Tepung Daun Indigofera (Indigofera zollingeriana) dalam Ransum Terhadap Karkas dan Non Karkas Ayam Broiler - Wijaya, Dadi; Falahudin, Aaf; Adam Yuliandri, Lili (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2025)
This study aims to analyse the carcass and non-carcass of broiler fed with rations resulting from the substitution of fish meal and soybean meal with indigofera (Indigofera zollingeriana) leaf meal (TDI) in the ration, as well as obtaining the balance of indigofera leaf meal substitution to produce the best carcass and non-carcass of broiler. This research method was conducted experimentally for 35 days using a completely randomised design (CRD). The treatment given in the form of substitution (TDI) as many as five levels, namely: P0 = 0% (as control),; P1 = Ration + 25% TDI; P2 = Ration + 30% TDI; P3 = Ration+ 35% TDI; P4 = Ration + 40% TDI. Each treatment was repeated 4 repetitions. The observed variables were live weight, weight after slaughter, carcass weight, carcass parts (breast, wings, back, and thighs), and non-carcass parts. The data obtained were analysed with ANOVA and further tested with Duncan's multiple range test. The results showed that both components and non-carcass parts of broiler decreased significantly after being given TDI in the ration. The average carcass weight in the control treatment was 833.75 ± 33.83 g. Whereas in the TDI treatment it ranged between 833.75 ± 33.83 g. While in the treatment of TDI administration ranged from 430.75 ± 25.81 to 491.00 ± 32.95 g. These commodities are also found in the components or parts of the non-carcass except the weight of blood. It can be concluded that the provision of TDI as a substitute feed ingredient for fishmeal and soybean meal as much as 25% or more is not able to increase the carcass or non-carcass components of broiler.